2017
DOI: 10.3389/feart.2017.00085
|View full text |Cite
|
Sign up to set email alerts
|

The Representativeness of Olea Pollen from Olive Groves and the Late Holocene Landscape Reconstruction in Central Mediterranean

Abstract: Modern pollen spectra are an invaluable reference tool for paleoenvironmental and cultural landscape reconstructions, but the importance of knowing the pollen rain released from orchards remains underexplored. In particular, the role of cultivated trees is in past and current agrarian landscapes has not been fully investigated. Here, we present a pollen analysis of 70 surface soil samples taken from 12 olive groves in Basilicata and Tuscany, two regions of Italy that exemplify this cultivation in the Mediterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Altogether, pollen from cultivated and synanthropic species form the sum of Anthropogenic Pollen Indicators (API) associated with human activities (Behre, 1981;Lopez-Saez et al, 2006;see Mercuri et al, 2013b for ubiquitous pollen taxa in archaeological sites of Italy). The OJC group, including Olea, Juglans and Castanea pollen, is an important marker of increasing anthropization in the Mediterranean area (Mercuri et al, 2013a;Florenzano et al, 2017) being sometimes constituted by the three curves (as in central Italy: Mercuri et al, 2002;Stoddart et al, this issue), or coinciding with only one or two of these tree pollen. Other woody plants, such as Vitis and Corylus, when cultivated, may be important cultural markers while the woody plants collected in the wild may be significant even if rare (e.g.…”
Section: Pollen As 'Land-use' Evidencementioning
confidence: 99%
“…Altogether, pollen from cultivated and synanthropic species form the sum of Anthropogenic Pollen Indicators (API) associated with human activities (Behre, 1981;Lopez-Saez et al, 2006;see Mercuri et al, 2013b for ubiquitous pollen taxa in archaeological sites of Italy). The OJC group, including Olea, Juglans and Castanea pollen, is an important marker of increasing anthropization in the Mediterranean area (Mercuri et al, 2013a;Florenzano et al, 2017) being sometimes constituted by the three curves (as in central Italy: Mercuri et al, 2002;Stoddart et al, this issue), or coinciding with only one or two of these tree pollen. Other woody plants, such as Vitis and Corylus, when cultivated, may be important cultural markers while the woody plants collected in the wild may be significant even if rare (e.g.…”
Section: Pollen As 'Land-use' Evidencementioning
confidence: 99%
“…These paleosols are rather poor in olive pollen, suggesting that olive trees did not grow in the immediate vicinity of the coastal sites 55 , 56 and see SI Appendix 5 . It has been shown that olive pollen is mostly abundant in soil samples derived from, or very near to, olive groves 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Greek colonial system on the coastal plain [58][59][60][61], and the agro-pastoral characterization of the inland indigenous sites [62][63][64][65]. Besides this, some specific issues that emerged from the research have been further explored (e.g., the value of Cichorieae as a pastoral indicator [66] and the Olea pollen representativeness in the modern local olive groves [67]).…”
Section: Previous Studies and The Aim Of This Papermentioning
confidence: 99%
“…Sustainability 2018, 10, x FOR PEER REVIEW 3 of 21 published, such as the environmental and economic settings of the rural sites of the Greek colonial system on the coastal plain [58][59][60][61], and the agro-pastoral characterization of the inland indigenous sites [62][63][64][65]. Besides this, some specific issues that emerged from the research have been further explored (e.g., the value of Cichorieae as a pastoral indicator [66] and the Olea pollen representativeness in the modern local olive groves [67]). This work focuses on the palynological evidence of pastoral/breeding activities in the studied archaeological records and explores the impact of centuries of grazing on the vegetation of Basilicata.…”
Section: Study Areamentioning
confidence: 99%